Edukacja partycypacyjna źródłem inspiracji w procesie resocjalizacji nieletnich - Sadowska, Magdalena (Kultura-Społeczeństwo-Edukacja, 2021)
The article contains considerations on the selected aspects of participatory education model in the process of juvenile rehabilitation. The background of the considerations is the regularities of cognitive and emotional development, as well as the process of shaping human identity in the period of adolescence. The use of the natural aspirations and needs of adolescents, reflected in the model of participatory education (in its values and methods), has become the basis for considerations regarding the implementation of this model in the process of juvenile rehabilitation (run in the conditions of a correctional facility).